On Abelian and Related Fuzzy Subsets of Groupoids - Seung Joon Shin; Hee Sik Kim; J. Neggers (The Scientific World Journal)
We introduce the notion of abelian fuzzy subsets on a groupoid, and we observe a variety of consequences which follow. New notions include, among others, diagonal symmetric relations, several types of quasi orders, convex sets, and fuzzy centers, some of whose properties are also investigated.